What are the factors of unhealthy financial behavior in the Muslim community of Metro Lampung City? - Nurlaili Nurlaili (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Financial behavior is one of the important things to be able to control personal finances, if healthy and good financial behavior can certainly manage cash flow well, the opposite can happen. Healthy and good financial behavior can certainly climb the level of prosperity. However, unhealthy and bad financial behavior will definitely reduce welfare status. Unhealthy financial behavior in this study is caused by people who are entangled in debts, have a consumptive nature, and have low self-awareness toward saving activities. The purpose of this study is to recommend to the Regional Government and the Central Government synergize with each other, building the mindset of the people on the outskirts of the metro city to rise together to climb the ladder of prosperity. The government is expected to be able to provide soft skill training for these people because most of the jobs for the people on the outskirts of Metro City are as laborers in the market. The results of this study, factors that lead to unhealthy financial behavior are caused by a low understanding of financial literacy because these people do not understand saving activities at the bank, do not understand insurance, and investment, have insufficient financial income, understand poor financial attitudes unfavorable and the influence of a strong external locus of control so that the outskirts of Metro City are entangled in debt and unhealthy financial behavior. Keywords: Financial Literacy, Financial Attitude, Income, Locus Of Control, Financial Behavior